FAKTOR-FAKTOR YANG MEMPENGARUHI RENTABILITAS PADA BPR DI KABUPATEN BLORA - Octa Artarina; Gregorius Masdjojo (Dinamika Akuntansi Keuangan dan Perbankan, 2013)
The aim of this research is to examine the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Expense to Operational Earnings (OEOE), Non Performing Loan (NPL) to the charge of Rentability wich is proxy by Return On Assets (ROA). The research uses purposive sampling method to collect data and uses multi linear regression model to analyze data. The result shows that partially LDR has a significant positive impact on ROA and BOPO has a significant negative impact on ROA. While CAR and NPL has insignificant impact on ROA. Then simultaneously CAR, LDR, BOPO, and NPL have significant effect on ROA. The Adjusted R Square is 0.51. This indicates the predictive ability of the five variables on ROA is 51 % of ROA's change is depend on the variables in the model and the remaining 49% are influenced bythe other factors.Key words: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), O